1985
DOI: 10.1161/01.hyp.7.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Renal and blood pressure responses to synthetic atrial natriuretic factor in spontaneously hypertensive rats.

Abstract: Atrial natriuretic factor (ANF) is a potent natriuretic and vasorelaxant agent that also stimulates guanosine 3',5'-cyclic monophosphate (cGMP) excretion in normotensive animals. These properties suggest that ANF may be involved in the regulation of blood pressure. To test a pure preparation of ANF in both normotensive and hypertensive animals, a synthetic 26 amino acid peptide (sANF) contained within endogenous rat ANF was infused intravenously into conscious Wistar-Kyoto rats (WKY) and spontaneously hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
13
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 16 publications
6
13
0
Order By: Relevance
“…53 Our finding of lower cGMP production by the in vitro incubation of glomeruli from 16-week-old SHR, together with a decreased density of glomerular ANF binding sites, suggests that the down-regulated receptor population is that associated with guanylate cyclase. Our results are compatible with those of Marsh et al, 54 who noted lower basal and ANF-stimulated urinary cGMP secretion rates in conscious SHR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…53 Our finding of lower cGMP production by the in vitro incubation of glomeruli from 16-week-old SHR, together with a decreased density of glomerular ANF binding sites, suggests that the down-regulated receptor population is that associated with guanylate cyclase. Our results are compatible with those of Marsh et al, 54 who noted lower basal and ANF-stimulated urinary cGMP secretion rates in conscious SHR.…”
Section: Discussionsupporting
confidence: 94%
“…54 In higher doses, a marked drop in blood pressure is observed in SHR accompanied by lower diuresis and natriuresis than in normotensive controls. This decrease of natriuresis with higher doses of ANF could be explained by a reduction in renal perfusion pressure, a well-known factor mediating the effect of the peptide.…”
Section: Discussionmentioning
confidence: 98%
“…In those studies, 15 the complete depressor dose-response relation for exogenous ANF and the dose-related potentiation of that activity by SQ 29,072 were characterized in conscious SHR, a model in which ANF produced a larger depressor response than in normotensive rats. 17 The present experiments extended that earlier work by examination of the renal responses to depressor doses of ANF-(99-126) in conscious, unrestrained SHR and provided additional evidence that a specific NEP inhibitor may prevent inactivation of ANF in vivo.…”
Section: Potentiation Of Renal Effects Of Atrial Natriuretic Factor-(supporting
confidence: 75%
“…Injection or sustained infusion of ANF showed a greater 11 or no 3 difference in systemic blood pressure drop in SHR, but there have been no reports on the response of pulmonary arterial pressure to ANF in SHR. Jin et al 23 showed the pulmonary depressor effect of ANF was significantly greater in hypoxia than in SL control Sprague-Dawley rats; however, there was no significant difference between experimental and control rats in the reduction of systemic arterial pressure.…”
Section: Discussionmentioning
confidence: 97%